Stay or go? Exploring physician turnover in European Hospitals–Evidence from the METEOR survey - Laura Maniscalco; Marco Enea; Peter de Winter; Neeltje de Vries; Anke Boone; Olivia Lavreysen; Kamil Baranski; Walter Mazzucco; Adriano Filadelfio Cracò; Malgorzata Kowalska; Szymon Szemik; Lode Godderis; et al. (PLoS ONE, 2025)
According to the World Health Organization (WHO), in 2022 there was a shortfall of approximately 1.2 million doctors, impacting healthcare system and patient care. Understanding turnover intentions is crucial for managing the healthcare workforce and ensuring continuous, and high-quality patient care. This study investigates the prevalence of physicians planning to leave their hospital or the profession, and risk factors such as job demand, resources, satisfaction, and burnout across four European countries. A cross-sectional multicenter study was conducted in eight hospitals across Belgium, the Netherlands, Poland and Italy, including both academic and non-academic institutions. Data from Poland were excluded due to a low response rate, to preserve respondent anonymity. Multivariable logistic regression analyses were performed, adjusted for country, demographics, and work context, using significant variables from the univariable analysis. The overall intention to leave the hospital was 16.5%, with the highest rates in Belgium (19.6%) and Italy (19%), and the lowest in the Netherlands (9.8%). The intention to leave the profession was 9.1%, with the highest rate in the Netherlands (16.1%), followed by Belgium (6.3%) and Italy (5.7%). Physicians at higher risk of leaving the hospital were younger (adjOR = 0.90, 95%CI = 0.86–0.93), lacked colleague support (adjOR = 3.18, 95%CI = 1.06–9.36), and were dissatisfied with job prospects (adjOR = 2.38, 95%CI = 1.02–5.54) and overall work (adjOR = 2.71, 95%CI = 1.09–6.69). Those more likely to leave the profession were from the Netherlands (adjOR = 4.14, 95%CI = 1.62–11.4), surgeons (adjOR = 2.90, 95%CI = 1.22–6.78), working in non-academic hospitals (adjOR = 2.43, 95%CI = 1.01–5.97), lacked development opportunities (adjOR = 5.97, 95%CI = 1.01–36.2), or were dissatisfied with career prospects (adjOR = 2.77, 95%CI = 1.04–7.27). Health system managers and relevant stakeholders involved in the planning, implementation, or evaluation of health policies and reforms aimed at improving healthcare job retention should take into account the key determinants of the intention to leave identified in this study.